2021
DOI: 10.3390/foods11010105
|View full text |Cite
|
Sign up to set email alerts
|

Meat Analogues in the Perspective of Recent Scientific Research: A Review

Abstract: There are many reasons why consumers and food producers are looking for alternatives to meat and meat products, which includes the following: health, environmental or ethical aspects. This study reviews recent scientific reports on meat analogues. The scope of the review includes the following: formulation and nutritional value; health safety and legal regulations; manufacturing and processing technologies including the latest developments in this area; product availability on the food market; and consumer att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 58 publications
0
46
1
4
Order By: Relevance
“…While traditional plant-based protein alternatives (such as tofu, seitan, and tempeh) are commonly accepted among vegetarians and vegans, companies are now creating alternatives, such as meat analogs that are intended to look, taste, and smell more like actual meat products, to increase their acceptability among omnivores [ 2 ]. It has been demonstrated that plant-based meat analogues are more acceptable than products produced from less known protein sources such as insects or in vitro cultured “meat” [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…While traditional plant-based protein alternatives (such as tofu, seitan, and tempeh) are commonly accepted among vegetarians and vegans, companies are now creating alternatives, such as meat analogs that are intended to look, taste, and smell more like actual meat products, to increase their acceptability among omnivores [ 2 ]. It has been demonstrated that plant-based meat analogues are more acceptable than products produced from less known protein sources such as insects or in vitro cultured “meat” [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we should think about moving towards the concept of “protein diversification”. Livestock-derived protein, aquaculture-derived protein, plant protein, marine protein, e.g., algae/seaweed, insects, protein from fermentation, e.g., mycoprotein and meat analogues [ 68 , 70 ] can all provide protein. This approach would embody a greater range of food options for the consumer, whilst the ratios in which these are consumed can be adjusted to align with health and sustainability policies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, consumers have paid particular attention to plant-based diets. This is due to the increasing public awareness of the health-promoting effects of bioactive compounds from plants on human health and the willingness to reduce meat consumption for environmental reasons [ 19 ]. Of particular importance in the diet are legumes, whose effect on inhibiting diseases has been scientifically confirmed.…”
Section: Protein Sources and Their Roles In Meat-alternative Productsmentioning
confidence: 99%
“…Meat processing methods and meat alternatives such as grilling, roasting, frying, and baking are considered methods that can lead to increased concentrations of carcinogenic substances such as heterocyclic aromatic amines [ 85 ]. However, using polyphenolic substances in plant-based products is easier than adding to meat products, which may lead to reduced HAA formation [ 19 ].…”
Section: Challenges For Protein Applications In Meat-alternative Prod...mentioning
confidence: 99%